Efficacy and tolerance of dolutegravir-based combined ART in perinatally HIV-1-infected adolescents: a French multicentre retrospective study. (13th December 2016) - Briand, Coralie; Dollfus, Catherine; Faye, Albert; Kantor, Elie; Avettand-Fenoel, Véronique; Caseris, Marion; Descamps, Diane; Schneider, Véronique; Tabone, Marie-Dominique; Vaudre, Geneviève; Veber, Florence; Blanche, Stéphane; et al.
Abstract : Objectives: To assess the safety and efficacy of a dolutegravir-based regimen in perinatally HIV-1-infected adolescents. Patients and methods: We conducted a retrospective multicentre study of 50 adolescents beginning dolutegravir-based treatment regimens between January 2014 and December 2015. Clinical and biological data collected before and after dolutegravir initiation were analysed. The primary endpoint was the proportion of patients achieving a plasma viral load (PVL) <50 copies/mL within 3 months of dolutegravir initiation (for patients with detectable viraemia at baseline) and maintaining virological suppression (PVL <50 copies/mL) until the last follow-up visit (for all patients). Results: Virological suppression was noted for 17/50 adolescents at baseline. Dolutegravir-based regimens maintained virological success in 14/17 patients (82%). The other three patients experienced a transient viral rebound, before PVL fell to < 50 copies/mL again, with no need to change the antiretroviral regimen. Thirty-three viraemic adolescents were enrolled. All but one had already received antiretroviral drugs. Virological success was achieved and maintained in 19/33 subjects (58%). Another three adolescents with initial virological failure had an undetectable PVL at the end of follow-up, with reinforced measures to improve compliance. Overall, sustained virological success was observed in 66% of patients and 78% of patients had an undetectable PVL at the last visit. Dolutegravir was well tolerated. Only one patient stopped treatment for severe drug-related adverse effects (dizziness and sleep disturbance). No emergence of resistance mutations was observed in patients with virological failure. Conclusions: Dolutegravir was safe and virologically effective in these patients, for whom multiple interventions were required to improve compliance.